The Efficacy of Remineralizing Materials on Artificial Enamel Lesions: An In Vitro Study - Gustė Klimaitė; Arūnas Vasiliauskas; Pranas Grinkevičius; Dominyka Grinkevičienė; Deivydas Šapalas (Medicina)
Background and Objectives: Contemporary caries treatment seeks to preserve hard dental tissues as well as to promote lesion remineralization and biological tissue regeneration. While fluoride-based treatments remain the gold standard, their effectiveness has limitations, prompting interest in innovative remineralization technologies. Nano-hydroxyapatite (nano-HA) varnish and self-assembling peptide (SAP) P11-4 are promising biomimetic materials that promote enamel repair, yet long-term data on their efficacy are limited. The objectives of this study were to evaluate the effectiveness of nano-HA varnish and peptide P11-4 in restoring enamel surface hardness after artificial lesions in vitro and to compare them to a control group and fluoride varnish. Materials and Methods: Artificial enamel lesions were created on the buccal surfaces of 36 extracted human molars, which were randomly divided into four groups (n = 9): control, peptide P11-4, fluoride varnish, and nano-hydroxyapatite varnish. After applying the materials as per manufacturer instructions, specimens were stored in artificial saliva for 14 days. Enamel surface hardness was measured using the Vickers hardness test (HV) at baseline, after demineralization, and after remineralization. Statistical analysis was performed with “IBM SPSS 27.0” using non-parametric Kolmogorov–Smirnov, Kruskal–Wallis, Dunn’s, and Wilcoxon tests. Results: The mean baseline enamel hardness value was 323.95 (SD 33.47) HV. After 14 days of demineralization, the mean surface hardness of artificial enamel lesions significantly plummeted to 172.17 (SD 35.96) HV (p = 0.000). After 14 days of remineralization, the mean value significantly increased to 213.21 (SD 50.58) HV (p = 0.001). The results of the study revealed statistically significant enamel remineralization of the peptide P11-4 group in regard to the demineralized enamel (p < 0.05). In contrast, there were no significant results in other treatment groups (p > 0.05). Remineralization of enamel was the highest in samples from the P11-4 group (54.1%), followed by the nano-HA group (35.4%), FV group (17.8%), and control group (11.2%). There was a significant difference (p < 0.05) in the remineralizing ability between the peptide P11-4 and all other treatment groups. Conclusions: Self-assembling peptide P11-4 effectively remineralized artificial enamel lesions and proved to be significantly more effective compared to fluoride varnish and nano-hydroxyapatite varnish, showcasing its superior performance as a remineralizing agent.